Kepimpinan instruksional guru besar di sekolah kurang murid / Zakaria Othman - Zakaria, Othman (2016)
A school is an educational institution, and its main purpose is implementing the curriculum through the teaching and learning process. With the concept of poverty in the context of school social deprivation, the purpose of this study was to analyse the state of instructional leadership in under enrolled schools, the students academic performance, teachers professionalism and the school climate, in the isolated and remote areas.The instructional leadership practices in under enrolled schools use Hallinger and Murphy’s Instructional Leadership Model (1985) which is divided into three dimensions, namely, setting school goals, managing the teaching programme, and encouraging school climate. In this study, the survey “Response Instructional Leadership Checklist Form” (Mc Ewan, 2003) was used and the respondents involved were 334 school headmasters across Malaysia. To view the instructional leadership practices in greater depth the researcher interviewed 6 school headmasters from selected under enrolled schools using an interview protocol adapted from the “Principal Instructional Management Rating Scale - Principal Form 2.0 PIMRS” (Hallinger, 1985).The study shows that the school headmasters from these under enrolled schools do practise the three dimensions of instructional leadership. However, dimensions of school climate are also commonly practiced by the school headmasters. The study also shows that there is a weak positive relationship between instructional leadership practices and students' academic performance. This is because students, parents, community, and the culture of the community living in isolated areas do not give much emphasis on education. The study also shows that: (i) under enrolled schools have good infrastructure facilities and are thus enabled to operate, (ii) school headmasters in these under enrolled schools are burdened with a heavy workload due to a lack of human resources (iii) under enrolled schools having students enrolment ≤ 30 students, cannot compete healthily (iv) school headmasters in these under enrolled schools who emphasize on teaching and learning process in the classroom are able to produce success in the school academic performance, (v) the role of community leaders and collaboration in the community can contribute to the success of these under enrolled schools , and (vi) modernization theory that links between technological progress and human development, has still not proven to bring positive impact to the indigenous people who live in the remote areas. Specifically, the study finds that the under enrolled schools in Malaysia are still relevant in fulfilling the democratic aspirations of our education system as stated in the Malaysia Education Blueprint (2013-1025). At the same time, the instructional leadership style should be adopted by every school headmaster in accordance with the District Transformation Programme (DTP), which proposes that the character of school leaders is no longer of ceremonial leader but more of instructional leader.